ANALISA PEMASANGAN APG(ALAT PELINDUNG GARDU) DALAM PENURUNAN GANGGUAN PENYULANG AKIBAT HEWAN DI PT PLN (PERSERO) ULP PERDAGANGAN - Karto Rizky; Adi Sastra P Tarigan; Solly Aryza (Ensiklopedia Education Review, 2022)
Electric power is produced by an electric power plant. Electric power from the generator cannot be used or sent directly to consumers, but must be transmitted and distributed first through a distribution substation. One of the problems faced is that there are frequent disturbances that result in unplanned blackouts. There are still many animal disturbances that make the use of the medium-voltage isolating transformer (TM) damaged, resulting in blackouts, as a result of unplanned blackouts there are many customer complaints received by PLN. . Substation protective equipment (APG) in the distribution substation network is a device that can withstand disturbances caused by animals which can reduce the number of unplanned blackouts.Keywords: Substation Protective Equipment.